PENGEMBANGAN INDUSTRI KREATIF PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) MELALUI EKSISTENSI MARKET ORIENTATION PERSPEKTIF SOSIAL - Dina Prasetyaningrum (Universitas Bina Taruna Gorontalo, 2024)
There are social business organizations that focus on market orientation, and these social business components come from processes that include intelligence generation, intelligence distribution, reaction design, and response implementation. Market orientation takes into account the marketplace needs of every industry, as well as the accountability of every business organization. The creative industry at UMKM is one social issue that can help the economy grow. The UMKM business can grow its operating units and sales by having a strong market orientation. The application of market orientation as a business strategy that is based on a social perspective and prioritizes the consumer as the primary customer in order for the theory of pricing to be operationalized. The research method uses the mix method using a sample of 30 respondents. Data analysis techniques with questionnaire data analysis on measuring the variables of intelligence generation, intelligence dissemination, response design, and response implementation as many as 32 items and technical interviews with MSME business actors. The results of the analysis of the questionnaire data for the total existence of market orientation in the Cilacap MSME creative industry were obtained at 79% consisting of the creative industry in the fashion sector 76% and the creative industry in the culinary field 82%. The existence of market orientation is not yet optimal based on the results of the interviews due to the lack of coordination, communication and regular management systems in the company.